Electronic Word of Mouth (E-WOM) Through the TikTok Application and Its Influence on the Purchase Decision of The Originote Skincare Products Among University Students in Yogyakarta - Dwiarini, Windy; Nyoman Udayana, Ida Bagus; Maharani, Bernadetta Diansepti (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the influence of Electronic Word of Mouth (E-WOM) via TikTok on purchase decisions for The Originote skincare among students in Yogyakarta. Using a quantitative method with purposive sampling, data from 184 respondents were analyzed through SmartPLS. Findings show that information quality, quantity, and credibility significantly affect information usefulness, which in turn influences purchasing decisions. This confirms that clear, relevant, and credible information on TikTok helps consumers assess products better and make confident decisions. The study emphasizes TikTok's strategic role in digital marketing for enhancing consumer trust and boosting online sales through informative content.